Effect Of Work Environment on the Safety and Occupational Health of Medical-Legal Directorate’s Staff - Ream I. Majeed; Dr. Taha Q. Ahmed; Dr. Sabeha M.Sheya; Dr. Ammirah J. Omar (Genius Journals, 2022)
The human element is the real fortune and the central axis in various places of work, therefore it is necessary to have safe work conditions to achieve health, safety and avoid facing risk. Laws and legislation have been enacted to protect people at work, to try hard the prevention of accidents , injuries and reduce the risks of the surrounded work environment.
Keywords: accidents; injuries; reduce; legislation